2018
DOI: 10.1039/c7sm01981e
|View full text |Cite
|
Sign up to set email alerts
|

The role of anions in adsorbate-induced anchoring transitions of liquid crystals on surfaces with discrete cation binding sites

Abstract: We report a combined theoretical and experimental effort to elucidate systematically for the first time the influence of anions of transition metal salt-decorated surfaces on the orientations of supported films of nematic liquid crystals (LCs) and adsorbate-induced orientational transitions of these LC films. Guided by computational chemistry predictions, we find that nitrate anions weaken the binding of 4'-n-pentyl-4-biphenylcarbonitrile (5CB) to transition metal cations, as compared to perchlorate salts, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 41 publications
1
65
0
Order By: Relevance
“…Additional discussion of the origin of the sigmoidal shape of the response curve evident in Figure 3ais given in the Supporting Information. [40] Previously, [17,29] we demonstrated that the dynamic response of LC films to chemical targets can be accelerated by lowering the density of the metal cation binding sites on surfaces to the minimum density required to achieve the initial homeotropic orientation of the LC.F urthermore,w e…”
Section: Zuschriftenmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional discussion of the origin of the sigmoidal shape of the response curve evident in Figure 3ais given in the Supporting Information. [40] Previously, [17,29] we demonstrated that the dynamic response of LC films to chemical targets can be accelerated by lowering the density of the metal cation binding sites on surfaces to the minimum density required to achieve the initial homeotropic orientation of the LC.F urthermore,w e…”
Section: Zuschriftenmentioning
confidence: 99%
“…Zuschriften showed that the cation surface density required to achieve ahomeotropic orientation of aLCdecreases with an increase in the strength of binding between the mesogen and metal cation binding site. [29] Guided by these prior design rules,w e investigated the use of LCs containing 4-(4-pentylphenyl)pyridine (PD,S cheme 1) [28] to generate ar esponse to Cl 2 . Table 1s hows that the binding energy of pyridine,t he surrogate for PD used in our computations,t oM n(ClO 4 ) 2 to be À1.75 eV,avalue that is 0.41 eV more negative than that of PhCN.Significantly,however,the binding energy of pyridine to MnO 2 is only À0.22 eV.Accordingly,these calculations led us to predict that LCs containing PD should transition from ahomeotropic orientation on Mn(ClO 4 ) 2 to aplanar orientation on MnO 2 upon exposure to Cl 2 with dynamics and sensitivity that exceed nitrile-containing LCs.B ecause PD does not form aL Ca sap ure component, we mixed it with 85 wt %nematic TL205 (Scheme 1) and confirmed mixing by using differential scanning calorimetry (Supporting Information, Figure S9).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 3 more Smart Citations